The Green Effect: Exploring the Impact of Innovation and Foreign Direct Investment on Environmental Quality in Malaysia - Ridzuan, Abdul Rahim; Dash, Santanu Kumar; Porwal, Ashish; Dhayal, Karambir Singh; Rahman, Nur Hayati Abd; Omran, Mohammed (International Journal of Energy Economics and Policy, 2023)
Do innovation and foreign direct investment (FDI) matter in greening the eco-system, and why not? They can lead to new technologies and knowledge, better efficient renewable energy, and reduced energy consumption; in turn this presumably reduces carbon emissions. In this study, we capture the short-and long-term impact of innovation and FDI, among other macro-variables, on the environmental quality in Malaysia using time series data over the period 1990-2020. Our empirical models find that both innovation and FDI have significant and positive impact on environmental quality in Malaysia, although it is only significant in the short-run for the first one, while significant in the long-run for the latter ones. The disappointing findings from our study is that both economic growth and urbanization show negative impact on environmental quality as CO2 tends to increase with higher levels of GDP and urbanization. An important policy recommendation that we can draw from this paper is that Malaysian policy-makers should, and foremost, focus on designing growth and urbanization policies, regulations and procedures that are environmentally induced to achieve decoupling goal in its development path. We believe that attracting more focused FDI that supports clean and green economy, better innovations and policies to replace traditional energy with clean and renewable ones, could achieve decoupling goal that leads to a reduction in CO2 emissions and improve environmental quality while keep growing in the world economy, including Malaysia.